Analisis Keabsahan Akad Murabahah Bil Wakalah Dalam Pembiayaan di Koperasi Sejahtera Al-Ikhlas Muslim Indonesia (KOSAMI) Perspektif Hukum Ekonomi Syariah - Hidayat, Sultan Nur; Irawan, Anggi; Anggraini, Rizki Dwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Sharia cooperatives are growing rapidly as microfinance institutions, with the Murabahah contract being the most widely used financing product. In practice, this contract is often combined with Wakalah to form the Murabahah Bil Wakalah scheme, where members are authorized to purchase their own needed goods. This study analyzes the implementation and validity of the Murabahah Bil Wakalah contract at the Koperasi Sejahtera Al-Ikhlas Muslim Indonesia (KOSAMI), reviewed in light of DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, PBI No. 7/46/PBI/2005, and sharia economic law. The method used is a qualitative method with an empirical juridical approach, through interviews with the chairman, administrators, and members of the cooperative, accompanied by observation and review of contract documents. Of the five suitability indicators analyzed, only two are met, namely the determination of a fixed margin and transparency of the cost price. Three other aspects have not been met: the financed goods never transferred ownership to the cooperative because they were purchased and registered in the member's name, the Wakalah and Murabahah contracts were signed simultaneously, and there was no recording of the transfer of ownership of the goods. These findings indicate that the implementation of the contracts at KOSAMI has not fully complied with the provisions of the fatwa and applicable regulations, so their validity according to Islamic economic law remains questionable. The study recommends that the cooperative ensure the transfer of ownership of the goods before the Murabahah contract is executed, separate the execution times of the two contracts, and complete the documentation of the handover of the goods.